Optimizing the amount of irrigation water and plant density in the cultivation of median corn cultivar (SC500) using response surface method - Shokooh Karimi; Aslan Egdernezhad; Mohammad Mehdi Nakhjavanimoghaddam (رویکردهای نوین در مهندسی آب و محیط زیست)
This research was conducted using corn data collected from a research farm in Karaj city. The studied treatments included three levels of irrigation (I1, I2 and I3 based on 75, 100 and 125% of the crop’s water requirement, respectively) and three planting densities (D1, D2 and D3 representing 75,000, 85,000 and 95,000 plants per hectare, respectively). This research was done in order to optimize the amount of irrigation water and plant density of corn. The results showed that the regression model used had a low estimation error (MBE<0), but its error and accuracy were acceptable based on two statistics, RMSE and NRMSE. The efficiency of this model was obtained based on two statistics d and EF (>0.9). For this reason, optimization was done using this model. Changes in yield, number of rows, leaf length and seed length had an upward trend with increasing irrigation water, but plant density only had an effect on increasing yield and seed length. The changes of other parameters did not have a regular trend, and for this reason, overlaying layers were used. The results showed that the optimal limits of irrigation water and plant density were in the range of -0.5 to +0.5. Based on the optimization results, if 85% of irrigation water is used and the plant density of 75,000 plants per hectare is observed, the highest yield and yield components are obtained.